Osteoarticular Tuberculosis-A Three Years’ Retrospective Study - Arathi N.; Faiyaz Ahmad; Najmul Huda (Journal of Clinical and Diagnostic Research, 2013)
Introduction: Extra pulmonary TB can be encountered in various organ systems, like lymph nodes, serous cavities, genitourinary tract, skeletal. Musculoskeletal TB can cause significant functional impairment. The clinical symptoms are variable, pain and swelling being common symptomatology. Investigations for suspected cases include radiological imaging, histopathological examination, bacteriological examination, and polymerase chain reaction. The mainstay of treatment is multidrug antitubercular chemotherapy. Aim: To study the cases of osteoarticular TB diagnosed on biopsy, to analyse the various microscopic patterns, results of microbiological investigations, correlate the clinical and radiological features and the response to ATT. Setting and Designs: A teaching tertiary medical institute in North India in catchment area, where prevalence of tuberculosis is high. A retrospective study of cases with a biopsy diagnosis of bone and/joint TB, retrieved from Histopathology section of Department of Pathology of the tertiary institute. Material and Methods: The study was retrospective and the data was collected for the preceding 3 years. The cases were retrieved from the records of the department of Pathology. A total of 16 cases were diagnosed as/suspected to be tuberculosis of bones and/joints. The clinical information were noted from the case files. Results of laboratory investigations along with relevant microbiologic investigations were noted. The biopsy samples were processed according to protocol. Ziehl–Neelsen stain to detect tubercle bacilli and PAS stain to rule out fungal infection were done. Microscopic features were noted. Results and Conclusion: Sixteen cases with a diagnosis of bone and/joint tuberculosis were found. The average age was 23.6 years. The most common presentation was pain and swelling. Knee joint was most commonly involved (7 cases) followed by spine and ankle (3 each). All the cases showed epithelioid granulomas which was necrotising in 11. AFB positivity was found only in 4 cases. ATT was started in 12 cases with a good response. It is important to suspect osteoarticular TB clinically and investigate accordingly. In resource poor setting, study of biopsy material can aid in diagnosis, further guiding the management.